2012
DOI: 10.1302/0301-620x.94b1.27001
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of a less invasive piriformis-sparing approach versus the standard posterior approach to the hip

Abstract: We undertook a randomised controlled trial to compare the piriformis-sparing approach with the standard posterior approach used for total hip replacement (THR). We recruited 100 patients awaiting THR and randomly allocated them to either the piriformis-sparing approach or the standard posterior approach. Pre- and post-operative care programmes and rehabilitation regimes were identical for both groups. Observers were blinded to the allocation throughout; patients were blinded until the two-week assessment. Foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
61
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 35 publications
2
61
0
Order By: Relevance
“…Previous studies assessing THA through the posterolateral approach mostly investigated the differences between the mini-incision and standard surgeries (19,20). In addition, operations with external rotator sparing mainly preserved the quadrate muscle of the thigh (8,21,22) or the piriformis muscle (9,11), while those sparing a larger extent of the short external rotator are scarce. In contrast to mini-invasive surgeries pursuing small incisions, muscle sparing operations do not necessarily minimize the incisions, thus having more indications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies assessing THA through the posterolateral approach mostly investigated the differences between the mini-incision and standard surgeries (19,20). In addition, operations with external rotator sparing mainly preserved the quadrate muscle of the thigh (8,21,22) or the piriformis muscle (9,11), while those sparing a larger extent of the short external rotator are scarce. In contrast to mini-invasive surgeries pursuing small incisions, muscle sparing operations do not necessarily minimize the incisions, thus having more indications.…”
Section: Discussionmentioning
confidence: 99%
“…Despite muscle suturing and reconstruction later during surgery, the trauma and in ammatory damage remain more pronounced than observed with the external rotator sparing approach. A randomized, controlled clinical trial of piriform-sparing THA showed that corrective surgery not only has the advantages of conventional posterolateral approach surgeries, but also involves the concept of mini-invasiveness (11). In this procedure, no osteotomy of the greater trochanter or resection of the piriformis muscle was required during the operation, and only piriformis muscle terminations on the articular capsule were dissected, resulting in signi cantly less trauma, reduced postoperative blood loss, and shortened hospital stay (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The short external rotator muscles and Iliotibial band are not violated, the hip is not dislocated, thus theoretically reducing the risk of postoperative dislocation. [38][39][40] The tissuesparing nature of this approach may allow for decreased time to ambulation, length of stay, 30-day readmission rates, in-hospital costs, and blood loss. [41][42][43] The purpose of the current study was to evaluate the incidence of dislocation at minimum one year follow up in a large series of patients undergoing primary, elective THA using the SuperPATH approach.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Surgical exposure of the hip joint is required for tumor surgery, treatment of infection in the hip joint, treatment of hip fractures, hemi-arthroplasty as well as primary and revised total hip replacement. [234567] The principles of surgical exposure include a thorough knowledge of anatomy of the region and its variations,[891011] proper patient positioning and adequate incisions. Dissections through natural cleavage planes help to minimize bleeding and disruption of important functional structures.…”
Section: Introductionmentioning
confidence: 99%